Problem Based Learning (Pbl) By Scaffolding and Reading Guide Model Strategies Toward the Quality of Learning - Hidayanto, Oktafian Endi; Wiyanto, Wiyanto; Purwanti, Eko (Universitas Negeri Semarang, 2021)
The level of student success in the learning process depends on the attention and interest of students. Application of appropriate learning models is expected to increase student interest in learning. The purpose of this study was to determine the effect of implementing the Problem Based Learning (PBL) model of the scaffolding strategy and reading guide on student learning activities and outcomes. This type of research is quantitative in the form of a quasi-experimental. The samples used were SDN Wonosari 02, SDN Wonosari 03, and SDN Tambakaji 02 Semarang. The sampling technique used non-probability sampling in the form of purposive sampling. The average activity value of the experimental class 1 is 76.44, the experimental class 2 is 73.87. The average post-test score for the experimental class 1 is 76.44, the experimental class 2 is 73.87. This shows that the activity and post-test scores of the experimental class I that apply the PBL scaffolding strategy model are better than those of the experimental class 2 who apply the PBL model of the reading guide strategy. The application of the scaffolding strategy in the form of giving cues, keywords and giving learning assignments that are tiered according to the level of student development makes students more independent in solving their own problems through teacher guidance. This study implies that the PBL scaffolding strategy model can be applied in the learning process.